Hubungan persepsi risiko dan tawakal dengan perilaku protektif covid-19 di pesantren dan asrama - Muhammad Zaki Afif Zainurrahman; Neng Wita Juwita Agustin; Amarria Ma’rufi (Fakultas Psikologi, 2021)
Islamic boarding schools and dormitories are one of the clusters with a high spread of COVID-19. The high intensityof clustering activities in these clusters can increase the potential for the spread of COVID-19. This study aims todetermine the differences in the level of risk perception, protective behavior, and tawakal (surrender to God) betweenindividuals living in Islamic boarding schools/dormitories and the general public. This present study is a mixed-methodresearch with scales and an open-ended question. All participants (N = 91) were Muslim with an age range of 18-24years. The data were analyzed using t-test and correlation tests for the quantitative data, and thematic analysis forthe qualitative data. The level of risk perception among participants living in Islamic boarding schools/dormitories islower than that of participants who do not live in these two places. The protective behavior between the two groups ofparticipants did not have a significant difference. We found a positive correlation between protective behavior andtawakal attitudes among participants living in Islamic boarding schools/dormitories. This study provides a deeperunderstanding on the dynamics of attitudes and behavior in Islamic boarding schools and dormitories during theCOVID-19 pandemic. Protective behavior among muslims is not only related to risk perceptions of a pandemic, butalso to tawakal as a religious manifestation in dealing with calamities.